The Effectiveness of Authentic Assessments during COVID-19: A Case of RMIT University in Vietnam (Comparative & International Education Series, 2021)
Vietnam has been one of the most successful nations in the fight against COVID-19 whereby the Vietnamese government has reacted quickly to the coronavirus by imposing strict social distancing rules and necessary lockdowns on various businesses and higher education institutions. The restricted access to campuses has required these higher education institutions to move all their teaching and learning activities online. Although the higher education institutions have made a relatively swift transition from offline to online with the help of several applications such as Zoom, Skype or Microsoft Teams, the main question is how the higher education institutions with an intensive implementation of authentic assessments like RMIT Vietnam deals with this situation. Therefore, this book chapter will investigate the effectiveness of authentic assessments during the COVID-19 period and explore whether authentic assessments work better (or worse) during this volatile period at RMIT Vietnam.